GAMBARAN KEJADIAN NYERI LEHER PADA PENGGUNA SMARTPHONE (Studi Di Pulau Jawa 2020) - Nadhifah, Nida; Udijono, Ari; Wuryanto, Moh. Arie; Saraswati, Lintang Dian (Jurnal Kesehatan Masyarakat (Undip), 2021)
In this global era, the use of smartphones is increasing and spreading throughout all ages. One of the effects of excessive smartphone use is neck pain. This study aims to describe neck pain in smartphone users. The population in this study are people domiciled on the island of Java who are more than 17 years. This study used a cross-sectional study design and quota sampling as a sampling technique with a sample size of 949 respondents. The results showed that 56.8% of respondents experience neck pain. 58,2% of women, 57,4% <30 years old, and 60,7% who use smartphone for ≥7 hours/day experience neck pain. . In conclusion, smartphone users in island of Java mostly experience neck pain, specifically women, respondents who are less than 30 years old and using smartphone for ≥7 hours/day. Limiting the use of smartphone and is needed to can prevent neck pain.